2023
DOI: 10.5624/isd.20220224
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of artificial intelligence using cone-beam computed tomography imaging of the oral and maxillofacial region: A scoping review and meta-analysis

Abstract: Purpose The aim of this study was to conduct a scoping review and meta-analysis to provide overall estimates of the recall and precision of artificial intelligence for detection and segmentation using oral and maxillofacial cone-beam computed tomography (CBCT) scans. Materials and Methods A literature search was done in Embase, PubMed, and Scopus through October 31, 2022 to identify studies that reported the recall and precision values of artificial intelligence systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…To date, few meta-analyses and systematic reviews have been conducted on the utilization of AI for PL detection [58][59][60][61][62][63][64]. An important study by Silva et al [60] showed that the pooled diagnostic accuracy of CBCT for PL detection was 88.75% (95% confidence interval = 85.…”
Section: Discussionmentioning
confidence: 99%
“…To date, few meta-analyses and systematic reviews have been conducted on the utilization of AI for PL detection [58][59][60][61][62][63][64]. An important study by Silva et al [60] showed that the pooled diagnostic accuracy of CBCT for PL detection was 88.75% (95% confidence interval = 85.…”
Section: Discussionmentioning
confidence: 99%
“…Several systematic reviews and meta-analyses have been conducted on the utilization of AI for identifying caries and periapical lucencies [44][45][46][47][48][49][50][51][52][53][54][55]. In a recent comprehensive study by Rahimi [54], the accuracy of classification models for caries detection was evaluated across 48 studies.…”
Section: Dental Diagnosticsmentioning
confidence: 99%
“…Cone beam computed tomography (CBCT) is a tool that provides three-dimensional volumetric data on maxillofacial structures and the assessment of airway area and volume [ 9 ]. The inclusion of AI for 3D image analysis enables the prediction of risk factors involved in diseases such as obstructive sleep apnea (OSA) syndrome [ 10 ], as well as speeding up the diagnosis and improving the data interpretation process [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%